Acknowledgment to Reviewers of Urban Science in 2020 - Urban Science Editorial Office (Urban Science, 2021)
Peer review is the driving force of journal development, and reviewers are gatekeepers who ensure that Urban Science maintains its standards for the high quality of its published papers [...]